ANALISIS RASIO KEUANGAN DALAM MENGUKUR NILAI PERUSAHAAN BERDASARKAN RASIO LIKUIDITAS, RASIO SOLVABILITAS DAN RASIO PROFITABILTAS PADA PT ELANG MAHKOTA TEKNOLOGI TBK PERIODE 2012-2021 - Fakung Rahman; Gatut Dradjad Purwoko; Tiffani Novia Rachmi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
This study aims to determine the effect of Current Assets (CR), Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Return On Assets (ROA) and Return On Equity (ROE) on Price to Book Value (PBV) at PT Elang Mahkota Teknologi Tbk for period 2012-2021. In this study the authors used causal associative research using a quantitative approach. The data analysis technique used in this study is multiple linear regression with the help of computer software, namely Statistical Product and Service Solutions (SPSS) Version 26. The sampling technique used was purposive sampling method with certain criteria and obtained a sample of 10 financial statements of Elang Mahkota Teknologi Tbk 2012-2021 period. The results of the t test show that CR, DAR and DER variables have no effect on PBV, while ROA and ROE variables have a positive effect on PBV. However, from the results of the F test together (simultaneously) CR, DAR, DER, ROA and ROE variables there is a significant effect on PBV variable. And the results of the R2 Determination Coefficient Test obtained a correlation coefficient value of 0.0947 or equal to 94.7%, which means that the relationship between CR, DAR, DER, ROA and ROE variables to PBV variable is in a very strong category, namely by 94.7% while 5.3% was influenced by other factors outside this model.